Real‐life use of digoxin in patients with non‐valvular atrial fibrillation: data from the RAMSES study. (27th September 2016) - Biteker, M.; Başaran, Ö.; Dogan, V.; Beton, O.; Tekinalp, M.; Çağrı Aykan, A.; Kalaycıoğlu, E.; Bolat, I.; TaŞar, O.; Şafak, Ö.; Kalçık, M.; Yaman, M.; et al.
Summary: What is known and objective: Although inappropriate use of digoxin has been described in various populations, a real‐world evaluation of patterns of digoxin prescription has not been well studied in patients with atrial fibrillation (AF). The aim of this study was to identify prevalence, indications and appropriateness of digoxin use in the general population of patients with non‐valvular AF (NVAF) in Turkey. Methods: We included and classified patients from the RAMSES (ReAl‐life Multicentre Survey Evaluating Stroke prevention strategies in Turkey) study, a prospective registry including 6273 patients with NVAF, on the basis of digoxin use. After excluding the data of 73 patients whose medical history about digoxin use or left ventricle function was absent, 6200 patients were included for the final analysis. Digoxin use was considered inappropriate if patients did not have left ventricular systolic dysfunction or symptomatic heart failure (HF). Results and discussion: Digoxin was used in 1274 (20·5%) patients. Patients treated with digoxin were older (71·4 ± 9·8 years vs. 69·2 ± 10·9 years, P < 0·001), more likely to be female (58·8% vs. 55·9%, P = 0·019) and had more common comorbidities such as HF (40·2% vs. 17·4%), diabetes (26·4% vs. 21·1%), coronary artery disease (35·3 vs. 27·6%) and persistent/permanent AF (93·4% vs. 78·4%; P < 0·001 for each comparison). Of the 1274 patients, the indication of digoxin use was considered inappropriate in 762 (59·8%). What is new and conclusion: Our findings show that nearly one‐fifth of the patients with NVAF were on digoxin therapy and nearly 60% of these patients were receiving digoxin with inappropriate indications in a real‐world setting. Abstract : Characteristics of patients by indication for digoxin use.